Aerodynamic Analysis of a Manned Space Vehicle for Missions to Mars. (23rd January 2011) - Pezzella, Giuseppe; Viviani, Antonio
Abstract : The paper deals with the aerodynamic analysis of a manned braking system entering the Mars atmosphere with the aim to support planetary entry system design studies. The exploration vehicle is an axisymmetric blunt body close to the Apollo capsule. Several fully three-dimensional computational fluid dynamics analyses have been performed to address the capsule aerodynamic performance. To this end, a wide range of flow conditions including reacting and nonreacting flow, different angles of attack, and Mach numbers have been investigated and compared. Moreover, nonequilibrium effects on the flow field around the entry vehicle have also been investigated. Results show that real-gas effects, for all the angles of attack considered, increase both the aerodynamic drag and pitching moment whereas the lift is only slighted affected. Finally, results comparisons highlight that experimental and CFD aerodynamic findings available for the Apollo capsule in air adequately represent the static coefficients of the capsule in the Mars atmosphere.